Review of membranes nanofiltration for treatment of water and wastewater - Farzad Mehrjo (Sustainable Earth Trends)
Today, a technology membrane nanofiltration has made significant progress in the treatment of pollutants from water and wastewater. This high-pressure technology has been able to produce high amounts of high-quality water. Features such as good pollutant removal capacity, low-cost membrane, reduced energy consumption, and long life of the nanofiltration membranes compared to reverse osmosis and environmentally friendly have made this technology popular in the world. Key features of nanofiltration membrane rejection are the low yield of monovalent ions, high return of divalent ions, and higher flux values compared to the membrane of reverse osmosis. These properties make nanofiltration membranes suitable for water and wastewater treatment, pollutants removal, pharmaceuticals, biotechnology, and foodstuffs engineering. Disposal of the nanofiltration membranes depends on a set of spatial effects, Donnan potential, dielectric, and conduction. Donnan's classical effect describes the balance and potential membrane interaction between a charged species and the interface of the charged membrane.